2020
DOI: 10.1002/onco.13519
|View full text |Cite
|
Sign up to set email alerts
|

Targetable BRAF and RAF1 Alterations in Advanced Pediatric Cancers

Abstract: RAF family protein kinases signal through the MAPK pathway to orchestrate cellular proliferation, survival, and transformation. Identifying BRAF alterations in pediatric cancers is critically important as therapeutic agents targeting BRAF or MEK may be incorporated into the clinical management of these patients. In this study, we performed comprehensive genomic profiling on 3,633 pediatric cancer samples and identified a cohort of 221 (6.1%) cases with known or novel alterations in BRAF or RAF1 detected in ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…BRAF fusions with partners AGAP3, TRIM24 and MKRN1 found in our study have also been previously reported to occur in CRC [15,16,34]. STARD3NL::BRAF fusion has earlier been described at least in one paediatric sarcoma [35], whereas to our best knowledge, LMTK2::BRAF has not been reported before in any tumour type. Two of the four Lung v2 NGS-detected RET fusions were detected by the Idylla assay as both RET-specific fusion and expression imbalance.…”
Section: Discussionsupporting
confidence: 84%
“…BRAF fusions with partners AGAP3, TRIM24 and MKRN1 found in our study have also been previously reported to occur in CRC [15,16,34]. STARD3NL::BRAF fusion has earlier been described at least in one paediatric sarcoma [35], whereas to our best knowledge, LMTK2::BRAF has not been reported before in any tumour type. Two of the four Lung v2 NGS-detected RET fusions were detected by the Idylla assay as both RET-specific fusion and expression imbalance.…”
Section: Discussionsupporting
confidence: 84%
“…The most significant results were extracted from a study of a large series of 3633 pediatric tumors screened for BRAF alterations: the sole two pPACC included in this series showed a PPP1CC::BRAF fusion in one case and BRAF mutation in the other case (Table 1 ). 13 Interestingly, the case with BRAF fusion also presented MYC amplification (formerly known as c‐MYC ). Cramer et al had also described a case of pPACC that harbored a BRAF (V600E) mutation associated with a MLL3 (R2463C) mutation (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient with SRGAP3-RAF-1 fusion also had a relatively more indolent course, responding to both surgical resection and chemotherapy. RAF-1 known activating fusions have previously been described in pediatric solid tumors 10,11. One study specifically comments on the SRGAP3:RAF1 fusion gene and its role in producing proto-oncogene through the MAPK pathways in pilocytic astrocytomas11 and another study described mutations in 5 distinct brain tumor subtypes, including pilocytic astrocytoma, and low-grade and high-grade glioma 10.…”
Section: Discussionmentioning
confidence: 99%
“…RAF-1 known activating fusions have previously been described in pediatric solid tumors. 10,11 One study specifically comments on the SRGAP3:RAF1 fusion gene and its role in producing protooncogene through the MAPK pathways in pilocytic astrocytomas 11 and another study described mutations in 5 distinct brain tumor subtypes, including pilocytic astrocytoma, and low-grade and high-grade glioma. 10 Our study adds an additional case to the literature describing 1 patient with a specific clinical course.…”
Section: Discussionmentioning
confidence: 99%